Comparative analysis of individual peculiarities for tennis players of different qualification - Y.O. Emshanova (Physical Education of Students, 2013)
A comparative analysis of indicators that reflect the personality characteristics of athletes of different skills. The study involved 36 athletes aged 14-26 years. Revealed the presence of significant differences in the level of mobility of nervous processes, the forces of braking, the severity indices of extraversion and neuroticism. Quality indicators of attention (concentration and speed of information processing) above highly skilled athletes. Indicators of anxiety (personal, reactive) is also higher in highly skilled athletes. Revealed that the athletes more skill, personality traits modified by the sport. These changes reduce the competitive stress, improving the performance, extend athletic career athletes tennis.